On the stereoselectivity of the cross metathesis of olefins catalyzed by a second-generation catalyst - J. Pablo Martínez; Bartosz Trzaskowski (Catalysis Communications, 2022)
Stereoselective control of the cross metathesis of olefins is highly desired in synthetic procedures. In this work, guided by thermodynamic and kinetic descriptors calculated using density functional theory methods, we performed an exhaustive exploration of the stereoselectivity of the cross metathesis of allylbenzene and 2-butene-1,4-diyl diacetate, catalyzed by a second-generation Grubbs catalyst. The kinetics of all possible propagation routes resulted in an E/Z 5:1 distribution of the metathesis product, in agreement with the experimental value of 7:1. Structural strain of olefins and activated catalyst was evaluated to reveal insights into the design of stereoselective catalysts within a strain-driven approach.